Evaluation of Poultry Egg Marketing in South-Western Nigeria - Afolabi, J.A. (International Journal of Poultry Science, 2007)
The study evaluated poultry egg marketing in Nigeria. It specifically identified the socio-economic characteristics of the respondents, examined the market structure for egg in the study area, determined the profitability of egg marketing and determined the influence of some socio-economic characteristics on the sales revenue of respondents. A multistage sampling technique was used to select 200 egg marketers in the study area and structured questionnaire administered on them. Descriptive statistics such as frequency and percentages were used to analyze the socio-economic characteristics of respondents while Gross margin analysis was employed to determine the profitability of the egg business in the study area. Gini coefficient was used to examine the market structure while production function was used to determine the influence of some factors on the sales revenue of respondents. The result showed that only 10% of the respondents were single while the remaining 90% were married. A literacy level of 70.50% was obtained among these marketers. Analysis also revealed that 67% of these marketers were retailers while only 10% were producer/sellers. The profitability analysis showed that an average marketer earned 4222.55 as gross margin per month. The Gini coefficient of 0.87692 obtained in this study indicates a high level of inequality in income among the respondents. The result also revealed that the regressors explained about 67.1% in the variability of the regressand.